What Structural Engineers and Fabricators Need to Know About Weld Metal - Miller, Duane K. (Engineering Journal, 1989)
To supply structural engineers and fabricators with the mechanical properties data needed to ensure good weldment design, manufacturers of consumables utilize standard filler metal qualification tests developed by the American Welding Society. Tensile properties are thus reported. Too frequently, engineers expect the results of these tightly controlled tests to be directly applicable to the properties of welded connections made in the shop or in the field. They are not. Both the structural engineer and the fabricator need to be aware of the ways in which many variables may affect the properties of the weld deposit. This paper will examine the purpose of filler metal qualification tests, the controls for these tests, and how production welds may deviate from the tests. Finally, guidelines will be discussed to enable the engineer to predict trends and assure that required strength levels are achieved.